2004
DOI: 10.1007/s00203-004-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoacetate generated by Rhodopseudomonas palustris from taurine

Abstract: Genes thought to encode (a) the regulator of taurine catabolism under carbon-limiting or nitrogen-limiting conditions and (b) taurine dehydrogenase were found in the genome of Rhodopseudomonas palustris. The organism utilized taurine quantitatively as a sole source of nitrogen (but not of carbon) for aerobic and photoheterotrophic growth. No sulfate was released, and the C-sulfonate bond was recovered stoichiometrically as sulfoacetate, which was identified by mass spectrometry. An inducible sulfoacetaldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
(39 reference statements)
3
46
0
Order By: Relevance
“…However, S. Weinitschke (unpublished data) has now observed that the addition of separated cytochrome c (from extracts of taurine-grown R. palustris) to the apparently inactive crude extract from R. palustris allows oxidation of taurine to sulfoacetaldehyde. This tends to confirm the hypothesis of Denger et al (2004b) that a native cytochrome c is sometimes essential for activity of taurine dehydrogenase. Correspondingly, characterization of taurine dehydrogenase will require not only pure protein (not attained elsewhere; Brüggemann et al, 2004) but also its native cytochrome c.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, S. Weinitschke (unpublished data) has now observed that the addition of separated cytochrome c (from extracts of taurine-grown R. palustris) to the apparently inactive crude extract from R. palustris allows oxidation of taurine to sulfoacetaldehyde. This tends to confirm the hypothesis of Denger et al (2004b) that a native cytochrome c is sometimes essential for activity of taurine dehydrogenase. Correspondingly, characterization of taurine dehydrogenase will require not only pure protein (not attained elsewhere; Brüggemann et al, 2004) but also its native cytochrome c.…”
Section: Discussionsupporting
confidence: 82%
“…The (N-methyl)taurine dehydrogenase from A. faecalis MT1 showed a much higher activity with the artificial electron acceptor, DCPIP, than with equine cytochrome c, as observed with some other taurine dehydrogenases (Brüggemann et al, 2004). One taurine dehydrogenase, postulated from the presence of the tauXY genes in Rhodopseudomonas palustris CGA009, is inactive with both DCPIP and equine cytochrome c (Denger et al, 2004b), which is itself an artificial substrate in bacterial extracts. However, S. Weinitschke (unpublished data) has now observed that the addition of separated cytochrome c (from extracts of taurine-grown R. palustris) to the apparently inactive crude extract from R. palustris allows oxidation of taurine to sulfoacetaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…The sulfur content of leaves is comprised mainly of sulfolipid and proteins; senescence of deciduous plants thus introduces significant amounts of sulfoquinovose into the soil (8). Sulfoacetate can also be the product of the bacterial assimilation of nitrogen from taurine (9,10). The latter precursor of sulfoacetate is a major organic solute in marine creatures (11,12) and in mammals (13), which excrete it in urine (14).…”
mentioning
confidence: 99%
“…3a, b). The assimilation of taurine-nitrogen sometimes involves utilization of the compound concomitant with growth, as found in Acinetobacter calcoaceticus SW1, Alcaligenes faecalis MT1 and Rhodococcus opacus ISO-5 (Denger et al, 2004a;Weinitschke et al, 2005Weinitschke et al, , 2006, and sometimes with excretion and subsequent utilization of the ammonium ion as in Rhodopseudomonas palustris CGA009 (Denger et al, 2004b), as shown in Fig. 3(b).…”
Section: Discussionmentioning
confidence: 93%
“…The compound can also serve as a sole source of sulfur for growth (e.g. Kertesz, 2000), and a range of phenomena can be involved when organisms utilize the compound as a sole source of nitrogen; these include deamination without desulfonation, not always concomitant with substrate utilization (Denger et al, 2004b;Styp von Rekowski et al, 2005;Weinitschke et al, 2005), and utilization concomitant with taurine carbon (Denger et al, 2004a). Two general pathways for the dissimilation of taurine have been hypothesized , one of which has received significant experimental support in Silicibacter pomeroyi DSS-3, especially for the genes encoding an ATP-binding cassette transporter (TauABC), taurine : pyruvate aminotransferase (Tpa) and alanine dehydrogenase (Ald) (analogous to Fig.…”
Section: Introductionmentioning
confidence: 99%